2021
DOI: 10.2147/dddt.s337925
|View full text |Cite
|
Sign up to set email alerts
|

New Progress in Improving the Delivery Methods of Bisphosphonates in the Treatment of Bone Tumors

Abstract: Bone tumors are tumors that occur in the bone or its accessory tissues, including primary tumors and metastatic tumors. The main mechanism of bisphosphonate is to inhibit the resorption of destructive bone, inhibit the activity of osteoclasts and reduce the concentration of blood calcium. Therefore, bisphosphonates can be used for malignant hypercalcaemia, pain caused by osteolytic bone metastasis, prevention of osteolytic bone metastasis, multiple myeloma osteopathy, improving radiosensitivity and so on. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…Common methods to promote bone repair, such as the use of growth factors, have little effect on inhibiting tumor recurrence . Previous reports showed that some studies used the controlled release of a variety of drugs to achieve the multi-effect of killing tumor cells and repairing bone defects, and some studies used the method of chemical synthesis to load drugs so as to achieve the delivery of drugs. ,, Nevertheless, there are still some problems bothering us. When multiple drugs are used, the effects of each drug may interfere with each other, and the use of multiple drugs may also increase the burden of liver and kidney, while the chemical synthesis may put forward a higher requirement for synthetic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Common methods to promote bone repair, such as the use of growth factors, have little effect on inhibiting tumor recurrence . Previous reports showed that some studies used the controlled release of a variety of drugs to achieve the multi-effect of killing tumor cells and repairing bone defects, and some studies used the method of chemical synthesis to load drugs so as to achieve the delivery of drugs. ,, Nevertheless, there are still some problems bothering us. When multiple drugs are used, the effects of each drug may interfere with each other, and the use of multiple drugs may also increase the burden of liver and kidney, while the chemical synthesis may put forward a higher requirement for synthetic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Bone related diseases such as osteomyelitis, osteosarcoma, osteoporosis are difficult to treat due to several limiting factors such as decreased perfusion of the bone, low bioavailability, toxicity and side effects. Therefore, designing drug delivery systems based on newer carriers such as microparticles, liposomes or nanoparticles that target the bone is a highly researched field [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Bisphosphonates induce apoptosis in osteoclasts [1], inhibit resorption of the destructive bone and the release of tumor stimulating factors [2]. Depending on the structure of the two terminal phosphate groups bisphosphonates may be divided into non-nitrogen containing bisphosphonates such etidronate and clodronate and nitrogen containing bisphosphonates such as alendronate, pamidronate, zoledronate, risedronate.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the role of antiresorptive BPs, they have direct functions such as antitumor [24], antiangiogenic [25], and anti-migratory [26] effects. Further, BPs are co-administered with doxorubicin, docetaxel, and paclitaxel [27][28][29][30][31] as cocktail therapies to treat bone metastasis. BPs are FDA-approved against osteoporosis, P Paget's disease, pediatric bone diseases [32], multiple myeloma, breast cancer metastasis, or prostate cancer to bone [33] as an adjuvant therapy to prevent metastatic bone pain.…”
Section: Introductionmentioning
confidence: 99%